2018
DOI: 10.1038/s41598-018-21058-w
|View full text |Cite|
|
Sign up to set email alerts
|

Far-UVC light: A new tool to control the spread of airborne-mediated microbial diseases

Abstract: Airborne-mediated microbial diseases such as influenza and tuberculosis represent major public health challenges. A direct approach to prevent airborne transmission is inactivation of airborne pathogens, and the airborne antimicrobial potential of UVC ultraviolet light has long been established; however, its widespread use in public settings is limited because conventional UVC light sources are both carcinogenic and cataractogenic. By contrast, we have previously shown that far-UVC light (207–222 nm) efficient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
198
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(221 citation statements)
references
References 40 publications
(43 reference statements)
5
198
0
5
Order By: Relevance
“…An exposure dose as low as 1.2 to 1.7 mJ/cm 2 of 222-nm light inactivates 99.9% of the airborne human coronavirus tested from both subgroups beta and alpha, respectively. Together with previous safety studies [12][13][14][15][16][17][18] and our earlier studies with aerosolized influenza A (H1N1) 23 , these results indicate that far-UVC light is a potentially powerful and practical approach for reduction of airborne viral transmission, without the human health hazards associated with conventional germicidal UVC lamps. Benchtop Aerosol Irradiation Chamber.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…An exposure dose as low as 1.2 to 1.7 mJ/cm 2 of 222-nm light inactivates 99.9% of the airborne human coronavirus tested from both subgroups beta and alpha, respectively. Together with previous safety studies [12][13][14][15][16][17][18] and our earlier studies with aerosolized influenza A (H1N1) 23 , these results indicate that far-UVC light is a potentially powerful and practical approach for reduction of airborne viral transmission, without the human health hazards associated with conventional germicidal UVC lamps. Benchtop Aerosol Irradiation Chamber.…”
Section: Discussionsupporting
confidence: 79%
“…We have previously shown that a very small dose (2 mJ/cm 2 ) of far-UVC light at 222 nm was highly efficient in inactivating aerosolized H1N1 influenza virus 23 . In this work we explore the efficacy of 222 nm light against two airborne human coronaviruses: alpha HCoV-229E and beta HCoV-OC43.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, far-UVC light in the 207-to 222-nm range has been demonstrated to effectively inactivate airborne aerosolized viruses. While preliminary findings from in vivo rodent models and in vitro three-dimensional (3-D) human skin models appear favorable to not cause damage to human skin and eyes (90,91), further research must be conducted to verify the margin of safety before implementation. If implemented safely, UVC and UVGI light offers a range of potential disinfectant strategies for buildings and is a common strategy for deep clean practices in health care settings.…”
mentioning
confidence: 99%
“…The floor and the walls of the procedure suite, recovery area and corridors will then undergo terminal cleaning with sodium hypochlorite solution 1000 ppm. Additionally, per our institutional protocol, ultraviolet C (UVC) light disinfection will be carried out by dedicated teams from environmental services [15]. The room will need to be aired for 20-30 min.…”
Section: Disinfecting the Procedures Roommentioning
confidence: 99%